(untitled) (Pulse, 2026)
Introduction: Whole blood donation is generally considered to be a safe procedure, but occasionally adverse reactions of varying severity may occur during or at the end of the collection. The aim of this study is to analyze the frequency and type of immediate adverse reactions occurring in whole blood donation. Material and methods: This was a record-based study conducted on all immediate adverse reactions related to whole blood donation performed over 36 months, from January 2019 to December 2021. After obtaining consent, donors were asked to complete a pre-donation questionnaire that gathered information on demographics and blood donation history. All donations were performed using 16-gauge needles from veins in the antecubital area after maintaining strict asepsis of venipuncture site. Blood collection was performed by trained technologists. Each donor was observed before, during and after donation for the occurrence of any adverse reactions. All reactions observed immediately after donation were recorded. Results: Overall, 168 adverse reactions were reported in relation to the 32,002 donations, resulting in an overall adverse reaction rate of 0.52%, that is, an incidence of 1 in every 191 donations. Majority of donors who experienced adverse effects were in age group of 18-25 years (66, 39.3%). First time donors had higher frequency (61,36.30%) for reactions. Vasovagal reaction of mild intensity was the most observed adverse reaction and accounted for approximately 72% of all adverse reactions noted. None of the donors with adverse reactions necessitated hospitalization. Conclusion: The risk of complications related to blood donation is low. Analysis of blood donation-related adverse events enables identification of at-risk donors and supports the implementation of targeted motivational strategies, effective predication counseling and optimized care during and after blood donation. Pulse Volume 17, Issue 2 2025; 15-19